2019
DOI: 10.1177/8756972819857881
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Valley of Death: Managing the When, What, and How of Innovative Development Projects

Abstract: The last few decades have seen a profound transformation of innovation project management within automobile firms. During the 1990s, the product development phase was revolutionized by the deployment of heavyweight project management, project portfolio processes, and platform strategies. The 2000s saw the forces of change move upstream in the innovation process, with the development of new methodologies intended to develop and orient creativity, as well as new upfront units acting as innovation labs. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Rather, they repeated and eventually enhanced their conventional project management practices. Those newer project management practices, such as the agile approach, which could be legitimate in innovation projects (Midler, 2019), were not legitimate in this project. This finding is in agreement with Lehtonen and Martinsuo (2008), who indicated that deeply embedded projects are more likely to ignore flexibility when adopting practices and procedures that are used in the parent organization, but inconsistent with Midler (2019), who found that innovative projects systematically question and transgress the best practices of head office departments.…”
Section: Project-permanent Organization Integration Conventional Proj...mentioning
confidence: 94%
See 1 more Smart Citation
“…Rather, they repeated and eventually enhanced their conventional project management practices. Those newer project management practices, such as the agile approach, which could be legitimate in innovation projects (Midler, 2019), were not legitimate in this project. This finding is in agreement with Lehtonen and Martinsuo (2008), who indicated that deeply embedded projects are more likely to ignore flexibility when adopting practices and procedures that are used in the parent organization, but inconsistent with Midler (2019), who found that innovative projects systematically question and transgress the best practices of head office departments.…”
Section: Project-permanent Organization Integration Conventional Proj...mentioning
confidence: 94%
“…Legitimacy and flexibility, viewed as a duality, could enable each other, like stability and change (Farjoun, 2010). Clark and Wheelwright (1992) and Midler (2019) found that firms that place high value on innovation adopt a heavyweight project management model to achieve the balance of legitimacy and flexibility, although they are in a highly institutionalized context. For example, organizations in the automotive industry, where radical innovation has become a key condition for competitiveness, put great commitment into innovation projects and embrace greater internal variation and openness, at the same time stabilizing their internal variation and institutionalizing their innovation.…”
Section: The Tension Between Legitimacy and Flexibility-project Imper...mentioning
confidence: 99%
“…Although at first related to new product development (NPD) processes (Midler, 2019a), it expanded to other organizational functions, leading to changes in hierarchy dynamics, task definitions, human resources management (Ingason et al, 2019) and work relationships (Arvidsson, 2009;Soderlund, 2006, 2010;Clegg and Burdon, 2021;Dollinger, 2020;Ekstedt, 2019;Nesheim, 2019;Prouska and Kapsali, 2021). It also created tensions due to the coexistence of both "permanent" and "temporary" organizational structures inside companies (Arvidsson, 2009;Ekstedt, 2019;Nesheim, 2019).…”
Section: Literature Review 21 the Phenomenon Of Projectificationmentioning
confidence: 99%
“…Projectification has been studied in varied contexts, such as entrepreneurship (Auschra et al, 2019;Li et al, 2020), public sector organizations (Godenhjelm et al, 2015), conservation of traditional rural biotopes (Cwikla and Jalocha, 2015;Raatikainen, 2018), health care (Glasdam et al, 2015;Marten and Sullivan, 2020;Penkler et al, 2020), pharmaceutical companies (Biedenbach, 2011), media broadcast (Clegg and Burdon, 2021) and in performing arts (Lindgren and Packendorff, 2007). From a geographic perspective, studies also examined the regional influences of projectification in European (Dornisch, 2002;Mukhtar-Landgren and Fred, 2019;Schoper et al, 2018) and in African countries (Bardosh, 2015;Marten and Sullivan, 2020) and as a crucial element to promote and coordinate collective innovation strategies in high-growth emerging countries (Clegg and Burdon, 2021;Midler, 2019a).…”
Section: Literature Review 21 the Phenomenon Of Projectificationmentioning
confidence: 99%
See 1 more Smart Citation